1999
DOI: 10.1007/s002109900070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous opioid receptor blockade on alcohol intake and up-regulation of opioid receptor subtype signalling in a genetic model of high alcohol drinking

Abstract: Effects of a continuous naloxone infusion via osmotic pumps on alcohol drinking and opioid receptor density and function in the high-drinking AA (Alko, Alcohol) rats were examined. AA rats were trained to drink 10% (v/v) ethanol in a 1-h limited access procedure and implanted with subcutaneous osmotic pumps delivering either saline, a low dose (0.3 mg/kg per hour), or a high dose (3.0 mg/kg per hour) of naloxone for 7 days. The pumps were then removed and alcohol, food and water intakes were measured for anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…In this respect, a particularly strong correlation has been reported for both (r ϭ 0.90) and (r ϭ 0.98) opioid receptors in rat brain (Hyytia et al, 1999). However, in an analogous study of DOR using DPDPE as both radioligand and agonist, only a tenuous correspondence was seen (r ϭ 0.61, nonsignificant; Hyytia et al, 1999). In the present study, radioligand binding revealed a highly significant Third, efficiency of coupling between DOR and G-proteins may be regionally heterogeneous, as has been proposed for mouse DOR (Oakley et al, 2003) and for rat MOR (Sim-Selley et al, 2000).…”
Section: S]gtp␥s Bindingmentioning
confidence: 84%
See 1 more Smart Citation
“…In this respect, a particularly strong correlation has been reported for both (r ϭ 0.90) and (r ϭ 0.98) opioid receptors in rat brain (Hyytia et al, 1999). However, in an analogous study of DOR using DPDPE as both radioligand and agonist, only a tenuous correspondence was seen (r ϭ 0.61, nonsignificant; Hyytia et al, 1999). In the present study, radioligand binding revealed a highly significant Third, efficiency of coupling between DOR and G-proteins may be regionally heterogeneous, as has been proposed for mouse DOR (Oakley et al, 2003) and for rat MOR (Sim-Selley et al, 2000).…”
Section: S]gtp␥s Bindingmentioning
confidence: 84%
“…In the main experiment, the sections were then incubated in assay buffer in the presence of a nonsaturating concentration of 0. Hyytia et al (1999). Sections were thawed at room temperature and rehydrated for 20 minutes in assay buffer containing 50 mM Tris-HCl, 5 mM MgCl 2 , 100 mM NaCl, and 1 mM EDTA (pH 7.4).…”
Section: I]delt Autoradiographymentioning
confidence: 99%
“…Slides were stored at Ϫ80°C until additional use. Agoniststimulated GTP␥S (a nonhydrolysable analog of GTP) binding was assessed using a procedure adapted from Hyytia et al (1999). Briefly, sections were thawed to room temperature and rehydrated for 20 min in assay buffer containing 50 mM Tris HCl, 5 mM MgCl 2 , 100 mM NaCl, and 1 mM EDTA, pH 7.4.…”
Section: Light Microscopic Immunolabeling Of Rat Brain Sectionsmentioning
confidence: 99%
“…Some previous work has demonstrated that ␦-opioid agonist-stimulated GTP␥S binding is greatest in the striatum (Hyytia et al, 1999). SNC86, SNC80, and SNC162 dose dependently stimulated […”
Section: In the [mentioning
confidence: 99%